Genotypic variability in the functioning of photosystem II in leaves of covered and naked oats - E. M. Lisitsyn; S. A. Churakova; G. A. Batalova (Труды по прикладной ботанике, генетике и селекции)
Background. Comparing the characteristics of primary photosynthetic processes in photosystem II (PSII) in the leaves of two oat (Avena sativa L.) subspecies will help to understand their genetic differentiation. Comparisons between naked and covered oats to assess the efficiency of energy flows within PSII and its relation to useful agronomic traits have not been previously made but can have an effect on their cultivation practices.Materials and methods. Two-week-old plants of 16 covered and 17 naked oat genotypes were assessed for rapid chlorophyll α fluorescence using a Fluor Pen FP 110/S fluorometer. Data on the yield structure were obtained in 2021. The data were processed statistically using descriptive statistics, correlation (Excel 2013) and cluster (StatSoft Statistica 10; Ward's method) analyses.Results. The groups of oat genotypes differed significantly in the absolute magnitude of adsorbed (ABS/RC) and trapped (TRo/RC) light energy flows, which were higher in naked oats (by 7.8 and 7.4%, respectively). The efficiency of electron transfer from plastoquinone QB to PSI in naked oats exceeded that in covered oats by 8.2%. For the whole set of genotypes, a statistically significant correlation of grain yield with the PIABS performance index (r = 0.403), light energy adsorption (r = -0.477) and its utilization at the reaction centers of PSII (r = -0.452) was manifested. The performance indices (PIABS and PIABS_total) positively correlated with part of grain in total biomass (0.571 and 0.418, respectively) and were higher in covered oats (by 28.2 and 21.9%, respectively).Conclusion. The existence of significant differences was shown between covered and naked oats according to six of the nine evaluated structural and functional parameters of the PSII leaf functioning. The results of the cluster analysis demonstrated the tendency to the grouping of genotypes by the presence/absence of grain hullness.